Potential of Kopasanda Leaf Ethanol Extract as Anti-Hyperglycemia - Hartati; Sahribulan, Sahribulan; Duprah, Nur Awaliah (Jurnal Biologi Tropis, 2024)
Indonesia has various types of plants that grow and spread naturally that have the potential as medicinal plants. Plants that are commonly used by the community as medicinal ingredients are kopasanda (Chromolaena odorata L.) or known as kirinyu. Kopasanda leaves contain several main compounds such as tannins, phenols, flavonoids, saponins and steroids. Essential oils from the leaves contain isomers of α-pinene, cadinene, camphora, limonene, β-caryophyllene and candinol. The flavonoid group has antioxidant activity including flavones, flavonols, isoflavols, isoflavones, cathexins, and chalcones, so that kopasanda leaves are rich in antioxidants that can lower blood glucose levels. According to the above description, the researcher will investigate the potential benefits of kopasanda leaf ethanol extract as an anti-hyperglycemia agent in mice. In this study, kopasanda leaves are extracted using an ethanol solvent, and the effect of the extract on the blood glucose levels of mice is tested. According to the findings, kopasanda leaf ethanol extract at a dose of 150 mg/kgBW significantly reduced blood glucose levels by 54.99%. The administration of kopasanda leaf extract significantly lowers blood glucose levels in mice, according to the findings. The ethanol extract of kopasanda leaves at a concentration of 150% is the most effective at lowering blood glucose levels, with a 54.99% reduction.